Direct and inverse theorems on the approximation of 2π -periodic functions by Taylor – Abel – Poisson operators - Prestin, J.; Savchuk, V. V.; Shydlich, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We obtain direct and inverse theorems on the approximation of 2π -periodic functions by Taylor – Abel – Poisson operators in the integral metric.